2020
DOI: 10.1055/a-1126-4272
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulating Effects Depend on Prolactin Levels in Patients with Hyperprolactinemia

Abstract: Prolactin is known to have immune modulatory effects acting through the prolactin receptor, which is present on a variety of immune cells. Certain chemokines contribute to form the type of T helper (Th) preponderance in the immune response. The objective of this work was to assess if hyperprolactinemia not related to pregnancy is associated with changes in circulating levels of chemokines and other immunological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“… 46 Moreover, PRL interferes with immune regulation by inhibiting the negative selection of autoimmune B lymphocytes, thereby promoting autoimmune reactions. 47 Prolactin receptors, widely expressed on immune cells, upon binding to prolactin, activate downstream signaling pathways that control the proliferation, differentiation, secretion, and survival of immune cells. 48 Drug-induced HPRL accounts for a significant portion of cases, with traditional antipsychotics being the most common culprits, associated with an incidence rate of 4.0%-70.0%.…”
Section: Discussionmentioning
confidence: 99%
“… 46 Moreover, PRL interferes with immune regulation by inhibiting the negative selection of autoimmune B lymphocytes, thereby promoting autoimmune reactions. 47 Prolactin receptors, widely expressed on immune cells, upon binding to prolactin, activate downstream signaling pathways that control the proliferation, differentiation, secretion, and survival of immune cells. 48 Drug-induced HPRL accounts for a significant portion of cases, with traditional antipsychotics being the most common culprits, associated with an incidence rate of 4.0%-70.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, diabetes with insulin resistance can directly contribute to an inadequate immune response, e.g., observed during COVID-19 ( 102 ) and some other severe acute viral infections. Prolactin and its receptors play an important role in regulating innate and adaptive immune responses ( 103 ), particularly in T lymphocyte growth and activation ( 104 , 105 ). Stimulation of angiotensin AT1 receptors is important for T cell activation and adhesion/transmigration through the basal endothelial membrane, whereas angiotensin AT2 receptors limit this effect ( 106 , 107 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been suggested that PRL levels may have immunomodulatory effects, influencing the immune response and contributing to the development of autoimmune thyroid diseases. 19 Additionally, thyroidreleasing hormone (TRH) stimulates the secretion of both PRL and TSH, which may lead to elevated PRL levels in patients with thyroid dysfunction. 20 The relationship between HPRL and TAI is not fully understood, but several potential mechanisms have been proposed.…”
Section: Discussionmentioning
confidence: 99%